Ultrastructure Morphology of Melastoma L. (Melastomataceae) Pollen. - Lilis Suryani; Fitria Ramona (Universitas Andalas, 2020)
Melastoma L. is the type genus of Melastomataceae. While Melastoma malabathricum is the type species with the mostwide spread distribution compared to other species in this genus. This research aim to study ultrastructure morphology of Melastoma pollen. The research was carried out by collecting species which included into Melastoma genus using survey method. Ultrastructure morphology of pollen was observed with Scanning Electron Microscope Type JSM-IT-200. Pollen samples originated from the pre-anthesis Melastoma flowers. The pollen was fixated, dehydrated and coated before observed, photographed and identified with electrone microscope. One species, M. malabathricum, has prolate spheroidal pollen. Four other species, M. setigerum, M. baccarianum, M.minahasae and M. malabathricum var. malabathricum, with oblate spheroidal pollen. The scanning results from electron microscope onto these five Melastoma species observed an aperture like a gap called colpus that varied in number. Pollen ornamentation resemble striate type on these five Melastoma species.